Review of polymers in the prevention of thermal runaway in lithium-ion batteries. (May 2020) - Allen, Jonathan
Abstract: Thermal runaway is one of the key safety concerns of lithium-ion batteries. The rapid increase in temperatures can result in catastrophic and often explosive failures of battery systems. Because lithium-ion cells have become the battery of choice in most portable gadgets, finding reliable and cheap methods to improve their safety is of economic importance. Application of materials within the battery is one of the most reliable ways to achieve this. Such methods are integrated into the battery itself, allowing for quicker responses as opposed to other monitoring systems. Polymers are among the materials highlighted to solve such safety concerns. Highly tuneable chemistries allow reliable employment of a positive temperature coefficient of resistivity (PTCR). This PTCR results in automatic battery shutdown when temperature increases beyond a certain threshold. However, this is often irreversible and further research improvements are required. This paper will highlight several known polymer materials and the methods in which they are employed to prevent thermal runaway within lithium-ion systems.